2023
DOI: 10.1111/apv.12368
|View full text |Cite
|
Sign up to set email alerts
|

The massifying consumption of embodied goods in an advanced capitalist state: Capital, economic anxieties and social networks

Abstract: Embodied goods like cosmetic surgery comprise a unique and growing consumer industry, most of all in the Asia‐Pacific, yet the rationalisation processes motivating their purchase are less understood. Addressing this lacuna, this article builds upon open‐ended surveys and semi‐structured interviews of consumers in Seoul, South Korea to articulate a relational approach to examine the rationalisation of purchases of cosmetic surgery as an embodied good. Theorised through the conceptual lens of Bourdieusian capita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The assembly of commodities recognized by consumers within the aesthetic space is termed the aesthetic cognitive space, a dynamic entity that undergoes changes over time. It consistently remains a subset of the overall aesthetic space of commodities (Chen, 2021;Au, 2023). When consumers assess commodities within the aesthetic cognitive space, various aesthetic values, such as shapes and colors, can be compared, establishing a quasi-order relationship among commodities.…”
Section: Quantitative Principles Of Aesthetic Experiencementioning
confidence: 99%
“…The assembly of commodities recognized by consumers within the aesthetic space is termed the aesthetic cognitive space, a dynamic entity that undergoes changes over time. It consistently remains a subset of the overall aesthetic space of commodities (Chen, 2021;Au, 2023). When consumers assess commodities within the aesthetic cognitive space, various aesthetic values, such as shapes and colors, can be compared, establishing a quasi-order relationship among commodities.…”
Section: Quantitative Principles Of Aesthetic Experiencementioning
confidence: 99%
“…These findings align with the findings of previous studies (Chiu et al, 2019;Khan et al, 2017;Souiden & Diagne, 2009) that social expectation has a positive and significant influence on males' intention to use skincare products. Au (2023) found that metrosexuals use skincare products to coordinate with social friends. The social expectation is highly considered in the consumption of male skincare products.…”
Section: Structural Modelmentioning
confidence: 99%